Der Dschihad und der Nihilismus des Westens: Warum ziehen junge Europäer in den Krieg? - Manemann, Jürgen (transcript, 2015)
Why does Jihadism EXERT such great fascination for young people in the Western world? Jürgen Manemann looks into the causes of this force of attraction by directing his attention to the cultural crises of Western societies: to feelings of emptiness, meaninglessness and hopelessness, and their consequences in the form of resignation, resentment and cynicism. Jihadism presents itself as a cure for these social maladies. Its effect, however, is only to intensify these crises, since it amplifies the inability to affirm life. As active nihilism, it produces an inability to empathize, which leads to hate and blind violence. Western societies must develop momentum to counter this by pursuing a consistent policy of recognition and sensitivity to suffering, thus re-strengthening the sense of a humanitarian culture.